Interprestasi Kesalahan Diksi Pada Berita Harian Online Akurat Jateng Edisi 12 November 2024 - Ina Hamung Putri; Dewi Astuti; Sri Muryati (Universitas Palan, 2025)
Online media has become the primary source of information for modern society due to its quick access and ease of news presentation. However, this development also poses challenges, particularly in maintaining writing quality, such as diction accuracy. Appropriate diction plays a crucial role in delivering clear messages, avoiding misunderstandings, and preserving media credibility. This study aims to analyze diction errors in the daily online news jateng.akurat.co edition of November 12, 2024, including non-standard word usage and word mismatches. This research employs a qualitative descriptive method to identify the types of errors, their causes, and their impacts on readers. Data were collected using documentation techniques by observing, recording, and analyzing the news texts published in the selected edition. The analysis process involved comparing diction usage with applicable linguistic norms and relevant contexts. The findings reveal several common errors, such as the use of terms that do not align with formal language norms, inappropriate word choices, and the improper adaptation of foreign words. Diction errors can create reader confusion, diminish media credibility, and affect perceptions of the information conveyed. This study highlights the importance of accurate diction selection in journalism, especially for regionally based media, which must consider cultural contexts and local values. These findings are expected to serve as a guideline for enhancing linguistic accuracy in digital journalism, maintaining media credibility, and supporting journalism's role as a pillar of a healthy democracy.